Microstructural Degradation of Ni/YSZ Electrodes in Solid Oxide Electrolysis Cells under High Current - Chen, Ming; Liu, Yi-Lin; Bentzen, Janet Jonna; Zhang, Wei; Sun, Xiufu; Hauch, Anne; Tao, Youkun; Bowen, Jacob R.; Hendriksen, Peter Vang (Journal of the Electrochemical Society, 2013)
Ni/yttria stabilized zirconia (YSZ) supported solid oxide electrolysis cells (SOECs) were exposed to long-term galvanostatic electrolysis tests, under different testing conditions (temperature, gas composition, current density etc.) with an emphasis on high current density (above −1 A/cm2). Detailed post-mortem characterizations were carried out to investigate microstructural changes after long-term galvanostatic tests, focusing on the Ni/YSZ electrode. Formation of ZrO2 nano-particles on Ni surfaces was observed in cells exposed to −1 or −1.5 A/cm2 at 800 or 850°C, but not in those tested at current densities below −0.75 A/cm2. The formation of ZrO2 nano-particles deteriorates Ni percolation and presumably decreases the number of active triple phase boundaries (TPBs) and is therefore considered a degradation phenomenon. It is hypothesized that the degradation of the Ni surface is a result of Ni-YSZ interfacial reactions, taking place under the conditions prevailing under strong polarization. A mechanism for the formation of ZrO2 nano-particles on the Ni surface under the electrolysis cell testing is proposed and the possibility of Ni-YSZ interfacial reactions under such conditions (T, p(O2)) is further elucidated by thermodynamic calculations.